Transfer of Rights on Land Because Sale and Purchase Which Have Not Been Certified and Its Rights Registration in The Land Office - Muhammad Mamduh Muzakki; Maryanto Maryanto (Jurnal Akta, 2019)
The purpose of this research is 1) To know the process of registration of transfer of land rights that have not been certified for sale and purchase and registration rights. 2) To determine the legal problems of transitional registration of land rights that have not been certified for sale and purchase and registration rights. 3) To know how the efforts and steps that should be done by the Land Office to resolve the legal problems of transitional registration of land rights that have not been certified for sale and purchase and registration rights.The method used is empirical juridical approach in order to obtain adequate results. Specifications research used in this study is a descriptive analysis, from this study is expected to obtain a detailed and systematic description of the problem to be studiedBased on data analysis concluded that: 1) The preparation of the deed of sale of land rights, advance PPAT shall conduct an inspection at the office of district / city land on the validity of the certificate of land rights are concerned. Second, the implementation PPAT deed to be attended by the parties concerned to take legal actions (seller and buyer) or a person authorized by him with written authorization in accordance with applicable laws and regulations. Third, the registration of transfer of rights, shall submit PPAT PPAT deed and other documents necessary for registration purposes transfer of rights over the land to the office of district / city land no later than seven business days. Fourth, delivery of certificates 2) According to the law for the transition of land rights for the sale and purchase of the land that is not registered is already eligible purchase material that is "Clear and" Cash ". 3) regardless of the procedure established by law. Therefore, for the people concerned to register their land are required to meet the specified requirements.Keywords :Transfer of Rights on Land; Purchase; Certified; Registration; Land Office.